Construction of Political Identity on Instagram: Unveiling the Kadrun Hashtag Movement in Indonesia's 2024 Presidential Election: Konstruksi Identitas Politik di Instagram: Menyingkap Gerakan Tagar Kadrun dalam Pemilihan Presiden 2024 di Indonesia - Ferry Adhi Dharma; Didik Hariyanto; Fajar Muharram (Academia Open, 2023)
This scientific article investigates the construction of political identity through hashtag movements on Instagram, focusing on the "#kadrun" hashtag related to Anies Baswedan, a presidential candidate for the 2024 election in Indonesia. Using the framing analysis method by Zhong Dang Pan and Gerald M. Kosicky, the study examines the structural dimensions of political identity content by observing and analyzing the hashtag from October 3, 2022, to May 3, 2023. The results reveal three Instagram accounts actively contributing and acting as political identity buzzers, uploading 89 to 92 contents within seven months. The hashtag frames Anies Baswedan and his supporters as a radical Islamic group, seeking to establish a caliphate, and intolerant, potentially leading to political polarization based on religion, community, and ethnicity in the upcoming election. These findings hold implications for understanding the impact of social media content on political discourse and polarization, especially among young active voters who rely on Instagram as a source of information during elections. Highlight: Research Scope: The study explores the construction of political identity on social media, particularly through hashtag movements on Instagram related to the 2024 presidential candidate in Indonesia, Anies Baswedan, and the "#kadrun" hashtag. Framing Analysis: Utilizing the framing analysis method by Zhong Dang Pan and Gerald M. Kosicky, the research examines the structural dimensions of political identity content on Instagram, focusing on message characteristics and content design from October 3, 2022, to May 3, 2023. The hashtag spreads messages identifying Anies Baswedan as a radical Islamic group, causing potential religious-based political polarization, as seen in the 2019 Election. Additionally, ethnic elements now contribute to polarization based on religion, community, and ethnicity in the 2024 elections. Keyword: Political Identity, Social Media, Hashtag Movements, Instagram, Political Polarization.